ISSR MARKER IN ACCESSING GENETIC DIVERSITY IN CHICKPEA GENOTYPES - DEEPANKAR PANDEY; ANUPAM BARH; MEENAKSHI JOSHI; ABHISHEK BALIYAN; PANKAJ (The Bioscan, 2001)
Genetic diversity is an essential component for Chickpea breeding. To access this genetic diversity in eighteen different genotypes, total of twenty ISSR markers were used, out of which seven ISSR primers, yielded a total of 37 amplified loci. Out of these 37 amplified loci, 32 loci were polymorphic whereas 5 loci were found monomorphic. The numbers of amplified loci varied from minimum of three to maximum of eight bands with an average of 5.28 loci per primer. It was lowest with Primer 8161-043 and Primer 8161-045 while highest with Primer 8161-049. One primers viz., Primer 8161-041 gave a total of one unique bands and this was unique to 612 bp for genotype PG105. Dendrogram based on UPGMA analysis of ISSR data grouped 18 genotypes in to four major clusters namely A, B, C and D. The cluster A had two genotypes. The major cluster B was sub divided into two groups B1 and B2 at the demarcation having 68.7 percent similarity. The group B1 included ten genotypes while group B2 comprised of four genotypes. The cluster C and D were found to be monogenotypic respectively. Based on estimated genetic similarity matrix, the highest genetic similarity value 0.930 was noticed between PG049 and PG081 while lowest similarity value 0.442 was noticed between PG105 and PG055. The study suggests that the genotypes PG105 and PG055are most genetically distant and beneficial for hybridization programmes to generate transgressive segregants. Current study also indicates that ISSR show mostly 100% polymorphism and acts useful tool in determining the genetic diversity and genotyping some of the chickpea accession regardless of environmental conditions.